Literature Review: Manifestation of the 5th Principle of Pancasila in Fulfilling the Education Rights of Children with Special Needs in Elementary Schools - Melati, Lina; Lorenza, Seillamitha Octaviona; Destiani, Wannuraniza; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
The principle of justice basically aims to realize democratic values and human rights. In terms of concept, justice contains four different meanings, namely equality, equity, giving proper personal rights, and divine justice. This research was conducted to analyze the implementation of the principles of social justice contained in the 5th principle of Pancasila regarding the fulfillment of the educational rights of children with special needs at the elementary school level. This research was conducted using the Systematic Literature Review (SLR) method. The findings of this research reveal the importance of implementing the 5th principle of Pancasila in ensuring the fulfillment of education for children with special needs (ABK) at the elementary school level. We found that there are several things that need to be considered in order to implement the 5th principle of Pancasila in an effort to fulfill the right to education for Children with Special Needs in Elementary School, namely: Equal access and opportunities in education, Respecting equal rights and obligations, Encouraging values love and tolerance, Having a wise attitude and the ability to solve problems, and Responding to challenges in implementing inclusive education and solutions.